Hubungan Forgiveness Dengan Subjective Well-Being Pada Remaja Yang Mengalami Perceraian Orang Tua - Jaquellin Cahyani; Nur Fitriany Fakhri; Muhrajan Piara (CV. ULIL ALBAB CORP, 2025)
The conditions experienced by teenagers who experience their parents' divorce cause them to receive negative stigma from their environment. Thus, it can lead to a lack of subjective well-being in teenagers who experience parental divorce. One of the internal factors that has the potential to influence an individual's subjective well-being is forgiveness. The aim of this research is to determine the relationship between forgiveness and subjective well-being in adolescents who experience parental divorce in Sulawesi. The subjects in this research were 388 teenagers who experienced their parents' divorce. The sampling technique in this research used accidental sampling. This research was measured using the Forgiveness and Subjective Well-Being scales. The analysis used in this research is simple linear regression with the help of IBM SPSS Statistics 25. The results of this research show that the significance value is p = 0.004 < 0.05, which means there is a relationship between forgiveness and subjective well-being. Meanwhile, the R Square value is 0.147, which means that there is a 2.64% contribution of forgiveness to subjective well-being in adolescents who experience parental divorce. The implications of this research provide an overview regarding forgiveness and subjective well-being in adolescents who experience parental divorce in Sulawesi.